Estudio de prefactibilidad para la instalación de una planta productora de aceite de coco - Noli Alva, Adela Devly (2019)
The present study has been done with the objective of determining the feasibility of installing a coconut oil production plant from the pulp of that fruit. This product is a healthy alternative to the common oils used.